Expression of recombinant human glutamylating TTLLs in human cells leads to differential tubulin glutamylation patterns, with only TTLL6 disrupting microtubule dynamics - Mohamed Aghyad Al Kabbani; Pragya Jatoo; Anne-Kathrin Klebl; Bert Klebl; Hans Zempel (PLoS ONE, 2026)
Polyglutamylation, a post-translational modification (PTM) catalyzed by a subset of Tubulin Tyrosine Ligase-Like (TTLL) family enzymes, regulates microtubule dynamics through its influence on interactions with microtubule-associated, motor, and severing proteins, and has recently also been implicated in genetic and neurodegenerative diseases. In this study, we characterized the glutamylation activity of various glutamylating TTLLs in human embryonic kidney 293T (HEK293T) cells, revealing distinct patterns of mono- and polyglutamylation among TTLL family members, with TTLL4 and TTLL11 exhibiting the strongest chain initiation and elongation activities, respectively. We found that TTLL6 expression uniquely decreased microtubule stability, with live-cell imaging of end-binding protein (EB3) showing a TTLL6-induced decrease in microtubule stability. To explore therapeutic modulation of TTLL activity, we tested LDC10, a novel TTLL inhibitor, which successfully blocked glutamylation across all TTLLs investigated in this study, while also reversing the microtubule-destabilizing effects of TTLL6. These findings identify a potential pathogenic role of TTLL6 in microtubule dynamics and highlight LDC10 as a promising pharmacological tool to counteract TTLL-induced microtubule destabilization.